Ethnography in pharmacy education (Research, Society and Development, 2022)
This research is a literature review that aimed to identify, describe and analyze studies that employed ethography in pharmacy education. The search was carried out in relevant scientific journals in the field of pharmacy education and health care professional education and in secondary databases. Five papers met the inclusion criteria, excluding papers that only presented theoretical and methodological discussions. They were analyzed according to the classic ethnographic characteristics: observational data collection process, the use of participant observation, the occurrence in natural environments, the use of multiple methods of date collection and the application of the reflexivity. The five studies cover pharmacy education in patient care. Regarding the methodology, only two studies presented all the characteristics described above. It is suggested, therefore, that future studies be developed in the field of pharmacy education with observation of such characteristics, increasing the rigor and quality of the results.